Pengaruh Inklusi Keuangan dan Pengelolaan Keuangan Terhadap Kinerja UMKM di Desa Rengasdengklok Utara - Kiki Carnasih; Rohma Septiawati; Meliana Puspitasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyse the impact of financial inclusion and financial management on SMEs. Financial inclusion refers to SMEs' access to financial services, while financial management encompasses the practices of managing funds and the effective use of capital. The unit of analysis for this research is SMEs in the village of Rengasdengklok Utara, with data collection conducted through the distribution of questionnaires. A sample of 65 respondents was targeted, but data was obtained from 58 respondents, with sampling conducted using purposive sampling technique. The analysis technique used is multiple linear regression analysis, which is a statistical method to determine the relationship between dependent and independent variables. This is because improved financial inclusion and financial management can enhance the overall performance of SMEs; financial inclusion provides financial access to business actors, while effective financial management can optimise the use of funds, thus these two factors can improve SME performance. For future researchers conducting similar studies, it is suggested that the sample size be larger and the data distribution more extensive. Furthermore, it is recommended to investigate variables such as social capital, financial technology, and more, to identify other factors that may influence SME performance..